S100B and Inflammatory Cytokine Levels in Blood as Potential Markers of Blood–Brain Barrier Damage and Psychiatric Impairment in Comorbid Hepatitis C Viral Infection and Alcohol Use Disorder. (28th June 2018) - Loftis, Jennifer M.; Valerio, Juno; Taylor, Jonathan; Huang, Elaine; Hudson, Rebekah; Taylor‐Young, Patricia; Chang, Michael; Ho, Samuel B.; Dieperink, Eric; Miranda, Juan Luis; Hauser, Peter
Abstract : Background: Hepatitis C virus (HCV) infection and alcohol use disorder (AUD) both adversely affect the immune system resulting in alterations in immune cell signaling and inflammatory processes. The aim of this study was to investigate how comorbid AUD contributes to abnormalities in inflammatory mediators and psychiatric impairments in adults with HCV. Methods: Alcohol use, mood, and inflammatory factors were evaluated at 3 time points (baseline, week 4, and week 12) in Veterans with HCV, with ( n = 42) and without ( n = 13) comorbid AUD. Peripheral indices of immune activation, blood–brain barrier (BBB) damage (S100 calcium‐binding protein B [S100B]), liver function, and viral load were measured using immunoassays and polymerase chain reaction assays. Results: Comorbid AUD was associated with increased symptoms of depression and anxiety, elevated levels of liver enzymes, and altered expression of inflammatory factors. Alcohol consumption was positively correlated with the severity of psychiatric symptoms. Univariate analysis identified significant group differences in interleukin (IL)‐8 ( p = 0.006), IL‐10 ( p = 0.03), and S100B ( p = 0.048), with increased levels in participants with AUD, which persisted over time despite reductions in alcohol use and no significant change in HCV viral load. Statistically significant effects of study group or time were not found for the other immune factors assessed. Exploratory receiver operating characteristic curve analysis evaluated the ability of IL‐8, IL‐10, and S100B to differentiate between levels of alcohol consumption and generated biomarker cutoff values used to identify low risk and unhealthy alcohol use groups. Conclusions: These results demonstrate that HCV and comorbid AUD are associated with greater psychiatric impairments, potentially resulting from increased inflammation, dysregulated cytokine expression, and compromised BBB function. Alcohol‐induced BBB damage may increase the risk of neuropathological consequences within the context of chronic HCV infection. Abstract : Alcohol use, mood, and inflammatory factors were evaluated across time in Veterans with hepatitis C virus (HCV) infection, with and without alcohol use disorder (AUD). Co‐morbid AUD was associated with increased symptoms of depression and anxiety, elevated liver enzymes, and altered expression of inflammatory factors (interleukin [IL]‐8 and S100 calcium‐binding protein B [S100B]), which persisted over time. Thus, HCV and co‐morbid AUD was associated with greater psychiatric impairments, potentially resulting from increased inflammation and compromised blood brain barrier function.